2013
DOI: 10.1371/journal.pone.0081224
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Domain Movements in Proteins Using Dynamic Contact Graphs

Abstract: A new method for the classification of domain movements in proteins is described and applied to 1822 pairs of structures from the Protein Data Bank that represent a domain movement in two-domain proteins. The method is based on changes in contacts between residues from the two domains in moving from one conformation to the other. We argue that there are five types of elemental contact changes and that these relate to five model domain movements called: “free”, “open-closed”, “anchored”, “sliding-twist”, and “s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…Relative domain movements were analysed using the DynDom website (Hayward & Berendsen, 1998;Hayward & Lee, 2002). The hinge and shear classification of the domain movements was determined using the dynamic contact graphs (DCG) method described by Taylor et al (2013Taylor et al ( , 2014. This The electron-density map for the DPM cofactor.…”
Section: Determination and Classification Of Domain Movementsmentioning
confidence: 99%
“…Relative domain movements were analysed using the DynDom website (Hayward & Berendsen, 1998;Hayward & Lee, 2002). The hinge and shear classification of the domain movements was determined using the dynamic contact graphs (DCG) method described by Taylor et al (2013Taylor et al ( , 2014. This The electron-density map for the DPM cofactor.…”
Section: Determination and Classification Of Domain Movementsmentioning
confidence: 99%
“…In the course of time, our work progressively demonstrated that this phenomenon could be observed in a wider range of proteins with little or no significant evolutionary relation to the previous ones [68]. Moreover, similarly to some protein folding methodological studies that “sees” the polypeptide chain as an assembly of particular sub-sets of smaller fragments orderable in a hierarchical process to yield the final protein architecture, such as: building blocks (microdomains), hydrophobic folding units (subdomains), protein domain, protein fold (multidomains) and quaternary structure [914], we have also located inside a number of protein primary structures, shorter amino acid sequences active against pathogenic microorganisms, potent opioids and hypotensive agents [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…At the all-atom level, a cut-off distance of 4 Å proved to be the most common optimal value, a distance that is often used as an atomic contact distance between non-bonded atoms, e.g. as in the contact of two domains in a protein (Taylor, et al, 2013).…”
Section: Discussionmentioning
confidence: 99%